Glucose status in cerebrospinal fluid (CSF) in different meningitic children in a hospital in Chittagong, Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Meningitis is referred to as an inflammatory process of the leptomeninges and cerebrospinal fluid (CSF) within the sub-arachnoid space of the brain. We have investigated glucose status in CSF in different types of meningitis together with detailed medical history in children. In addition, we have also carried out the detailed cytological and microbiological examinations. A total of 40 subjects were investigated. We observed that the glucose level was significantly decreased (